Participation of Muslim Women in Islamic Philanthropy in Digital Era: Malaysian Experience - Mekwok Bt Mahmud; Nor Amni Bazilah Bt Mohd Zain; Raudlotul Firdaus Bt Fatah Yasin (Afkaruna: Indonesian Interdisciplinary Journal of Islamic Studies, 2019)
In general, Islamic Philanthropy is an important instrument that can solve the socio-economic problems of a country. The ultimate goal of Islamic Philanthropy is to benefit the economy and the society, which began during the time of Prophet Muhammad S.A.W. and has been continuously developed to this day. This research aimed to investigate the participation of Muslim women in Islamic philanthropy in the digital era, specifically their contributions to the waqf institutions in Malaysia. History and present times have shown evidence of significant contributions of women in Islamic Philanthropy as founders, beneficiaries, and mutawallis or trustees. This research conducted a library search, seeking evidence of selected Malaysian experiences of women’s participation in Islamic Philanthropy in the past and at present. The expected result was an analysis of Malaysian experiences in the participation of Muslim women in Islamic Philanthropy institutions in this digital era, and to identify the need for improvements of the socio-economic conditions of the society.